Alergia a la vacuna Pfizer-BioNTech® demostrada mediante pruebas cutáneas - Estrada García, Carlos David; Macías Robles, Ana Paola; Cortés Grimaldo, Rosa María; Carvajal Alonso, Hilda Lilian; Barreto Alcalá, Marlen; Ramírez Nepomuceno, Adriana; Esparza Amaya, David; Coronado Hernández, Kareli Guadalupe; Barrios Díaz, Britza; Campos Téllez, Héctor Hugo (Revista alergia Mexico (Tecamachalco, Pueblo, Mexico : 1993), 2023)
Background: The Pfizer-BioNTech BNT162b2 vaccine, provides 95% effectiveness from the second dose onwards. The reported rate of anaphylaxis to COVID-19 vaccines is 4.7 cases/million doses administered. Case presentation: 30-year-old female, health professional, history of allergic rhinitis, asthma, reaction to eye cosmetics and adhesive tape: erythema, edema and local pruritus. Immediately after application of the first dose of Pfizer-BioNTech vaccine, she presented grade III anaphylaxis. The patient was stratified, phenotyped and skin tests with PEG 3350 were positive. A recommendation was issued not to reapply vaccine containing polyethylene glycol and alternatives were offered. Discussion: An adequate risk stratification should be performed before applying mRNA-based COVID-19 vaccines for the first time in at-risk groups. In case of anaphylaxis at the first dose, phenotyping and further study with PEG skin tests should be performed and vaccination alternatives should be offered. Introducción: La vacuna Pfizer-BioNTech® BNT162b2 proporciona efectividad del 95% a partir de la segunda dosis. La tasa de anafilaxia reportada de vacunas para COVID-19 es de 4.7 casos por millón de dosis administradas. Reporte de caso: Paciente femenina de 30 años, profesional de la salud, con antecedentes de rinitis alérgica, asma, reacción a productos cosméticos en los párpados y al pegamento de la cinta adhesiva (eritema, edema y prurito local). Posterior a la aplicación de la primera dosis de la vacuna Pfizer-BioNTechÒ tuvo un evento de anafilaxia grado III. Se estratificó, fenotipificó y efectuaron pruebas cutáneas con PEG-3350, que resultaron positivas. Se sugirió no aplicar la aplicar vacuna de refuerzo que contuviera polietilenglicol y se ofrecieron alternativas de tratamiento. Conclusión: Es importante efectuar la adecuada estratificación de riesgo antes de aplicar las vacunas para COVID-19 basadas en ARNm por primera vez. En caso de anafilaxia es necesario fenotipificar y ampliar el estudio con pruebas cutáneas con PEG, además de otorgar alternativas de vacunación.